Artificial Intelligence in Recruitment: A Case Study of Moroccan Recruitment Agencies - Meena, Pushkar Raj; Panda, Khirod Chandra (Journal of Global Economy, Business and Finance, 2025)
The integration of artificial intelligence into recruitment processes has brought substantial improvements to recruiters' routines, thereby enhancing the efficiency of this function. It is in this context that this article addresses this theme, delving deeply into the significance of AI usage and its impact on the tasks of recruitment managers. Furthermore, this article aims to highlight the various applications of AI throughout the different phases of the recruitment process. It also seeks to decipher the perceptions of recruitment managers regarding the use of this technology while identifying the benefits it provides as well as its limitations. To achieve these objectives, a qualitative approach was adopted, relying on semi-structured interviews conducted with around ten recruitment managers from Moroccan and multinational recruitment agencies. The results from the survey indicate that artificial intelligence is emerging as a promising tool in the field of recruitment in Morocco, capable of enhancing the overall efficiency of the recruitment process. Nevertheless, it is imperative to implement it thoughtfully to avoid potential limits.